Impact of Direct and Indirect Tax on the Nigerian Economic Growth - Ogundana, Oyebisi Mary; Ogundana, Oyedele Mary; Ogundana, Oyeyemi Mercy; Ibidunni, Ayodotun Stephen; Adetoyinbo, Adebola (Bina Nusantara University, 2017)
This research examined the direct and indirect impact of taxation on the Nigerian economic growth. This research centered on two major objectives by focusing on the trend of direct and indirect tax and the impact of the Nigerian tax system on the growth of the economy.Â The research adopted the descriptive research design.Â The secondary source of data was also engaged as this data was from CBN statistical bulletin and the annual reports from 1994-2013. The research also used the ordinary least square regression technique. With the use of E-views 7.1 to analyze the data, the first objective was achieved by using graphical analysis while the second objective used ordinary least square regression analysis. The results reveal that the direct and indirect tax have a positive impact on the economy of Nigeria. Therefore, it is recommended that government should take advantage of taxation and promote tax system in Nigeria.